POSTMENOPAUSAL BLEEDING - A STRONG INDICATOR OF ENDOMETRIAL CARCINOMA - Jadoon, Saima; Khan, Shah Muhammad; Qadir, Maimoona; Bibi, Nagina (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the demographic profile, patterns of bleeding and histopathological patterns of endometrial biopsy in women presenting with postmenopausal bleeding. Study Design: Descriptive cross sectional study. Place and Duration of Study: Gynaecology and Obstetrics Department, MTI/Mardan Medical Complex, Mardan Pakistan, from Apr 2016 to Mar 2017. Material and Methods: This descriptive cross sectional study was included women of any parity and age >45 years who had spontaneous cessation of menstruation for the last one year while premenopausal women, drug or irradiation induced or iatrogenic menopause were excluded. All patients were admitted, transvaginal ultrasound done (cut off endometrial thickness >4mm) and subjected to dilatation and curettage under anesthesia and endometrial biopsies obtained. Samples were sent for histopathology and followed. Results: A total of 35 women were included. Commonest age group was 61-70 years, and was seen in 19 (54.3%) women, followed by 52-60 years age group where 9 (25.7%) subjects were observed. Mean age was 62 ± 2.54 years. Twelve (35%) women were hypertensive while Type 2 Diabetes Mellitus (T2DM) was seen in 7 (20%). Twenty (57%) women complained of streak of blood on sanitary pad, and in 28 (80%) there were recurrent episodes. Twenty four (68.57%) women were multiparous. Atrophic endometrium was the most common benign histopathological pattern, seen in 9 (26%) followed by 8 (23%) chronic endometritis. Endometrial carcinoma was seen in 8 (23%) subjects with endometroid carcinoma in 28 (80%) cases. Conclusion: Postmenopausal bleeding is an alarming symptom and should be thoroughly investigated with transvaginal ultrasound followed by endometrial biopsy for timely diagnosis and treatment.